Comparative Efficacy of Mindful Self-Compassion Therapy and Acceptance and Commitment Therapy on Alexithymia and Pain Anxiety in Employed Women with Migraine - Adeleh Yousefi Siakoucheh; Mohammad Narimani; Nader Hajloo (مجله علوم پزشکی صدرا, 2025)
Introduction: Migraine headaches, as a neurogenic disorder, significantly impact patients’ psychological well-being. This study aimed to compare the effectiveness of Mindful Self-Compassion Therapy (MSCT) and Acceptance and Commitment Therapy (ACT) in addressing alexithymia and pain anxiety among employed women with migraine.Methods: This study employed a quasi-experimental design with a pretest-posttest framework with a control group. The target population comprised employed women suffering from migraine headaches in Rasht (Iran), in 2023. A purposive sampling method was used to select 60 participants, who were then randomly allocated into three equal groups (n=20 per group, two intervention groups, and one control group). Assessment tools included the Toronto Alexithymia Scale (TAS-20), measuring difficulty identifying feelings, difficulty describing feelings, and externally oriented thinking, and the Pain Anxiety Symptoms Scale (PASS-20). Both intervention groups received eight 90-minute sessions of their respective therapies. Data were analyzed using multivariate analysis of covariance (MANCOVA) in SPSS software (version 26).Results: After controlling for pretest scores, significant between-group differences emerged in posttest measures of alexithymia components (difficulty identifying emotions, difficulty describing emotions, externally oriented thinking) and pain anxiety. However, no significant differences (P>0.05) were observed between the MSCT and ACT groups’ outcomes at post-test.Conclusion: Both MSCT and ACT demonstrated comparable efficacy in mitigating the psychological consequences of migraine, particularly in reducing alexithymia and pain anxiety.